Cost-utility of preventive interventions for breast cancer in Peru - Aguado, Alfonso Gutiérrez (2013)
Objective: To determine the cost utility of preventive interventions  against breast cancer in Peruvian women. Design: Cost-utility type economic evaluation. Material: Epidemiologic parameters, costs. Interventions: A cost utility analysis using Markov model based on the information of epidemiological parameters, costs associated with breast cancer and usefulness was performed. Costs were from the payer perspective (Health Ministry) compared with adjusted life years (QALYs) and used a discount rate of 5%. Main outcome measures: Incremental cost-effectiveness ratio. Results: The annual cost of breast self-examination intervention was USD 10 410 811, for clinical breast examination was 45 007 733.76, with mammography was USD 46 624 661.45 and for intervention with tamoxifen was $ 4 705 800. The incremental cost-effectiveness ratio (RICE) was 2 639.6 USD / QALY.Conclusions: The intervention with mammography was more cost-effective than other interventions. Key words: Breast neoplasms, mammography, tamoxifen, costeffectiveness analysis (source: MeSH NLM).